Logistics practices in healthcare organizations in Bogota. Issue 3 (6th August 2018) - Velasco, Nubia; Moreno, Juan-Pablo; Rebolledo, Claudia
Abstract : Purpose: The purpose of this paper is to explore the current state of logistics practices in healthcare organizations in Bogota, Colombia. Design/methodology/approach: The assessment is based on case study research using open interviews, focused interviews, a questionnaire and direct observations as sources of evidence. Seven Colombian health care settings are analyzed: four public hospitals and three private clinics. Cross-case analysis allows the identification of patterns regarding supply management, inventory management, replenishment and use of information and communication technologies. Findings: Manual procedures, poor planning, little recognition from top management and a lack of specialized personnel characterize the current situation. Innovative practices with a potential to improve the efficacy of logistics activities are rare, particularly in public hospitals. Research avenues: Future research could replicate this study in other Colombian cities, in order to generalize the results to the whole country. It could also be interesting to document successful and less successful implementations of innovative logistics practices in Colombian hospitals to guide and promote their adoption. Research limitations/implications: The small number of cases considered, and the fact that the research is concentrated in one city, limits the generalizability of the results. Originality/value: To the best of the authors' knowledge, this research is the first to explore the state of healthcare logistics practices in Colombia. Abstract : Objetivo: Este artículo explora el estado actual de las prácticas logísticas en los hospitales de Bogotá, Colombia. Diseño/metodología/enfoque: La evaluación se basa en la investigación de un estudio de caso utilizando entrevistas abiertas, entrevistas centradas, un cuestionario y observaciones directas como fuentes de evidencia. Se analizan siete establecimientos de salud colombianos: cuatro hospitales públicos y tres clínicas privadas. El análisis cruzado de casos permite la identificación de patrones relacionados con la gestión del abastecimiento, la gestión de inventarios, la reposición y el uso de las tecnologías de la información y la comunicación (TIC). Resultados: Los procedimientos manuales, la mala planificación, el escaso reconocimiento de la alta dirección y la falta de personal especializado caracterizan la situación actual. Las prácticas innovadoras con un potencial para mejorar la eficacia de las actividades logísticas son raras, particularmente en los hospitales públicos. Investigación futura: Este estudio se podría replicar en otras ciudades colombianas, con el fin de generalizar los resultados a todo el país. También podría ser interesante documentar implementaciones exitosas y menos exitosas de prácticas logísticas innovadoras en hospitales colombianos para guiar y promover su adopción. Limitaciones de la investigación/implicaciones: El pequeño número de casos considerados, y el hecho de que la investigación se concentra en una ciudad, limita la generalización de nuestros resultados. Originalidad/valor: Según nuestro conocimiento, esta investigación es la primera en explorar el estado de las prácticas de logística hospitalaria en Colombia.